Intrinsically low lattice thermal conductivity in layered Mn3Si2Te6 - Qingfang Li; Yingbing Cheng; Delin Zhao; Yineng Huang; Xiangang Wan; Jian Zhou (New Journal of Physics, 2023)
The ferrimagnetic nodal-line semiconductor Mn _3 Si _2 Te _6 has recently received much attention due to its colossal angular magnetoresistance (Seo et al 2021 Nature 599 581). The magnetic and electronic properties of Mn _3 Si _2 Te _6 have been extensively studied. Meanwhile, a recent experiment showed that Mn _3 Si _2 Te _6 has a low in-plane lattice thermal conductivity, which implies its potential applications in thermoelectricity. Here, we have investigated phonon dispersion and lattice thermal conductivity of Mn _3 Si _2 Te _6 by the first-principles calculations and the Peierls–Boltzmann transport equation. It is found that the lattice thermal conductivities of Mn _3 Si _2 Te _6 are quite low, which are 1.33 and 0.96 Wm ^−1 K ^−1 along the a and c axes at 300 K, respectively. A significant contribution (>90%) to the thermal conductivity comes from the acoustic phonons and low-frequency optical phonons linked to the vibration of Te atoms. Meanwhile, it is found that such low thermal conductivities of Mn _3 Si _2 Te _6 are a consequence of the low group velocities and relatively short phonon lifetimes, which are intrinsically derived from the quite complex crystal structure, heavy Te atoms, and relatively weak chemical bonding. Our work not only explains the origin of the intrinsically low thermal conductivity of Mn _3 Si _2 Te _6 but also could be helpful to the study on the thermal conductivity of other similar layered magnetic materials.